American Economic Association Universal Academic Questionnaire Summary Statistics - E., Scott, Charles; J., Siegfried, John (American Economic Review, 2017)
American Economic Association Universal Academic Questionnaire Summary Statistics by Charles E. Scott and John J. Siegfried. Published in volume 107, issue 5, pages 678-80 of American Economic Review, May 2017